Australian Studies at the Lodz University: Co-operation Between the British and Commonwealth Studies Department, University of Lodz, and the Australian Embassy in Poland - Kujawińska Courtney, Krystyna (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The article discusses the history of academic co-operation between the British and Commonwealth Studies Department at the University of Lodz and the Australian Embassy in Poland. Over the years the co-operation took the shape of a regular academic exchange and led to substantial academic, educational and cultural projects on Australia which resulted in a number of book-length studies.